The Effect of the Source of Bud Set Material and Auxin Concentrations to the Growth and Production of Sugarcane (Saccharum officinarum L.) - Yohannes Kristian Immanuel Hutapea; meiriani meiriani; Asil Barus (Jurnal Agroekoteknologi, 2018)
The growth and production of sugarcane are mainly affected by the quality of seedling, source of bud set material and the use of plant growth regulators as a factor influencing the quality of seedling that is produced so that the amount of production will be affected. The purpose of this research is to obtain the best source of bud set material and auxin concentration for the growth and production of sugarcane. This research was held in a PT. Perkebunan Nusantara II nursery in Tanjung Jati, Kecamatan Binjai Barat (50 above the sea) on July 2016 until April 2017. This research used a randomized block design with two factors, they are the source of bud set material (top stem and under stem material) and auxin concentrations (0 NAA+0 NAAm,100 ppm NAA+25 ppm NAAm, 200 ppm NAA+50 ppm NAAm, 300 ppm NAA+75 ppm NAAm and 400 ppm NAA+100 ppm NAAm). The result of this research showed that the source of bud set materal which is originally from the under stem material was significant increasing the growth of tillers and the stems as well as the source of bud set material that is originally from the top stem material that was really increasing the growth of stem diameter and the number of plant segments. The different auxin concentrations treatment was not significant increasing the growth and production of sugarcane. The treatment interaction of source of bud set material and auxin concentrations was not significant affecting to the growth and production of sugarcane.